SIKAP MAHASISWA JURUSAN PENDIDIKAN LUAR BIASA, FAKULTAS ILMU PENDIDIKAN, UNIVERSITAS NEGERI JAKARTA (PLB-FIP, UNJ) TERHADAP PENINGKATAN KETERAMPILAN SOSIALISASI ANAK TUNAGRAHITA MELALUI - Siti Nuraini Purnamawati (Fakultas Ilmu Pendidikan Universitas Negeri Padang, 2016)
This research aims to figure out the position of attitude of undergraduate students of special education programmes, Faculty of Education, State University of Jakarta toward improvement socialisation skills of students with intellectual disabilities through inclusive education. This research used likert scales. The sample of this research was 30. This study used purposive sampled. The reliability of the instrument used Alpha Cronbach is 0.96 compared to r table on a= 0.05 is 0.63. Data analysis used planagan formula. Score limit for positive position is 27% from top’s scores and negative position is 27% from bottom’s scores. The highest score is 123 and the smallest score is 89. Score average is 105.16. The result figure out the attitude of undergraduate students in between positive and negative